The impacts of the Arid Lands Resource Management Project (ALRMPII) on livelihoods and vulnerability in the arid and semi-arid lands of Kenya - Johnson, Nancy L.; Wambile, A. (International Livestock Research Institute, 2011)
There is an urgent need for new approaches and effective models for managing risk and promoting sustainable development in arid and semi-arid lands (ASALs), especially in the face of climate change and increasing frequency of drought in many areas. This study assesses the impacts of the Arid Lands Resource Management Project (ALRMPII), a community-based drought management initiative implemented in 28 arid and semi-arid districts in Kenya from 2003 to 2010. The project sought to improve the effectiveness of emergency drought response while at the same time reducing vulnerability, empowering local communities, and raising the profile of ASALs in national policies and institutions. In this evaluation, multiple data sources and analytical methods were used to assess impacts on the project’s five key performance indicators (KPIs). The evaluation focused on 10 randomly selected districts. Data sources included a household panel data set (505 households), anthropometric measurements (>600,000 observations), 21 focus group discussions in project intervention communities, a survey of 95 response agencies, and key informant interviews. Though the project was not implemented according to an experimental framework, where appropriate difference-in-difference analysis was used to assess impact on indicators.